Competition-Based Device-to-Device Transmission Scheduling to Support Wireless Cloud Multimedia Communications - Runan Yao; Wei Wang; Sung Shin; Seong H. Son; Soon I. Jeon (International Journal of Distributed Sensor Networks)
Multimedia applications based on cloud services for mobile devices have recently gained considerable popularity. However, the increasing density of devices leads to a high level of interference, which reduces the performance of wireless communication between devices and cloud. In this paper, we propose a new approach which allows the network to adaptively find a transmission opportunity scheduling strategy by choosing the most valuable transmission request opportunity. In this approach, the transmission request selection strategy is optimized by considering multimedia distortion reduction, hidden node problem, transmission interference, and signal coverage. Simulation results show that the proposed request selecting strategy significantly improves the systems overall data transmission quality by exploring the tradeoff between communication node pair and their neighbor nodes.